Rancang Bangun Aplikasi Pelaporan Kegiatan Guru Pendamping Kelas Sekolah Inklusif Se Kota Surabaya - Irfan Kurniawan Pratama Ardianto; Pantjawati Sudarmaningtyas; Ignatius Adrian Mastan (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Inclusive school is a school which has regular students and also disability students. In Surabaya there were 70 inclusive schools, With so many the number of schools cause dinas difficulty in showing data are sprouting the capabilities of students inclusive , know the development of the total students inclusive. For teachers reporting documents to cause teachers must commutes collecting the document to Dinas Pendidikan. Based on of problems that emerged, can be given a solution that education authorities need an application that can assist in the reporting process of teaching and learning activities in schools and recaps in knowing the developmental ability of students inclusive. This program designed web based to solve problem. This application is designed Based on the results of the test system by using the black box and white box that has created the application can solve problems that occur by displaying developmental ability students - inclusive, is able to determine the amount of growth students - inclusive, helping teachers in accelerating the process reporting. Web based in order to solve the existing problems.Keywords: Application, Inclusive Teacher Reporting, Inclusive Schools